RECENT TRENDS ON SOCIAL ISOLATION AND LONELINESS AMONG OLDER PEOPLE IN ITALY - Lamura, G. (Innov Aging, 2017)
This presentation will provide a basic understanding of how social isolation and loneliness in older age are experienced in Italy. Through the use of both national data and findings from comparative studies, it will be highlighted how social and economic trends are affecting older Italians in this regard, including relationships and contacts with family members, neighbours, friends and the wider society. The connection with elder abuse will be also analysed, as a clear association has been found between social isolation and elder abuse. Finally, recent evidence suggests also that migrants might experience these phenomena differently than native Italians. In particular, findings concerning the Albanian and Moroccan ethnic groups (two of the largest in the country) show that their relatively large networks of close family members and other relatives protect them from social isolation, but not from loneliness, due to the lack of relationships with non-kin co-ethnic peers.